# SOLUTION: 7x-6y=-8 x-9y=7 (x,y)=

Algebra ->  Algebra  -> Expressions-with-variables -> SOLUTION: 7x-6y=-8 x-9y=7 (x,y)=      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Expressions involving variables, substitution Solvers Lessons Answers archive Quiz In Depth

 Question 391188: 7x-6y=-8 x-9y=7 (x,y)=Answer by haileytucki(390)   (Show Source): You can put this solution on YOUR website!7x-6y=-8_x-9y=7 Since -9y does not contain the variable to solve for, move it to the right-hand side of the equation by adding 9y to both sides. 7x-6y=-8_x=9y+7 Replace all occurrences of x with the solution found by solving the last equation for x. In this case, the value substituted is 9y+7. 7(9y+7)-6y=-8_x=9y+7 Multiply 7 by each term inside the parentheses. 63y+49-6y=-8_x=9y+7 Since 63y and -6y are like terms, add -6y to 63y to get 57y. 57y+49=-8_x=9y+7 Since 49 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 49 from both sides. 57y=-49-8_x=9y+7 Subtract 8 from -49 to get -57. 57y=-57_x=9y+7 Divide each term in the equation by 57. (57y)/(57)=-(57)/(57)_x=9y+7 Simplify the left-hand side of the equation by canceling the common factors. y=-(57)/(57)_x=9y+7 Simplify the right-hand side of the equation by simplifying each term. y=-1_x=9y+7 Replace all occurrences of y with the solution found by solving the last equation for y. In this case, the value substituted is -1. y=-1_x=9(-1)+7 Multiply 9 by each term inside the parentheses. y=-1_x=-9+7 Add 7 to -9 to get -2. y=-1_x=-2 This is the solution to the system of equations. y=-1_x=-2